Analisis Kesulitan Belajar Bahasa Arab Terhadap Mahasiswa - A'yuni, Rizka Qurrota; Lathifah, Hamidatul; Al Faruqi, Mhd Ibnu Hanan; Mustofa, Syaiful (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Factors that cause difficulties in learning Arabic are internal and external factors. This research aims to analyze the factors of difficulty learning Arabic. This research uses a qualitative approach with descriptive methods. Data collection techniques use interviews and documents. Data analysis in the form of data reduction, data classification, data analysis and conclusions. The object of this research is based on Arabic language education master's students at UIN Maulana Malik Ibrahim Malang 2023 and Arabic language education students at UIN Alauddin Makassar 2023. The results of this research explain that difficulties in learning Arabic are caused by three factors, including differences in students' educational backgrounds, weak mastery. Arabic vocabulary, as well as lack of interest and motivation to learn. The differences in students' educational backgrounds include graduates of Islamic boarding schools, Madrasah Aliyah, and superior schools. Weak mastery of Arabic vocabulary includes qawaid and tarkib, aswat arabiyah as well as imla and insha. Meanwhile, lack of interest and motivation includes the weak role of parents, teachers and self-motivation. Based on these difficulty factors as evaluation material in learning Arabic to achieve the expected learning outcomes